BaMtox, a Myotoxic Enzyme Isolated from the Venom of the Bothrops Alternatus - Lívia Maria Alves; Bruno Tumang Frare; David Colares Achê; Lamartine Lemos de Melo; Mirian Machado Mendes; Veridiana Melo Rodrigues; Luiz Fernando Moreira Izidoro (Journal of Skeletal Muscle, 2022)
Snake envenomations are responsible for a high percentage of deaths, as these toxic proteins induce severe local and systemic effects. In Brazil, the Bothrops genus is responsible for a satisfactory fraction of accidents, including Bothropsalternatus, recognized as urutu, whose venom is capable of inducing severe myotoxicity. In this work, the BaMtox toxin was purified through a combination of three chromatographic steps, ion exchange in DEAE-Sepharose, affinity in Benzamidine Sepharose 6B columns and reversed-phase HPLC chromatography on a C18 column. The BaMtox toxin has a molecular mass of approximately 14kDa and did not show phospholipase activity or hemorrhage. On the other hand, it induced edema and a significant increase in plasma levels of the creatine kinase enzyme. Thus, the protein called BaMtox is able to induce myotoxicity.
Keywords: Snake